Associations between punitive policies and legal barriers to consensual same-sex sexual acts and HIV among gay men and other men who have sex with men in sub-Saharan Africa: a multicountry, respondent-driven sampling survey. Issue 3 (March 2023) - Lyons, Carrie E; Twahirwa Rwema, Jean Olivier; Makofane, Keletso; Diouf, Daouda; Mfochive Njindam, Iliassou; Ba, Ibrahima; Kouame, Abo; Tamoufe, Ubald; Cham, Bai; Aliu Djaló, Mamadú; Obodou, Evelyne-Patrice; Karita, Etienne; et al.
Summary: Background: Few assessments of associations between structural-level factors and HIV among gay men and other men who have sex with men (MSM) have been conducted, especially in sub-Saharan Africa. Our objective was to examine HIV testing history, HIV status, and stigmas among MSM living in ten countries with heterogeneous legal environments. Methods: This study used pooled data from ten country-specific, cross-sectional studies done in 25 sites in Burkina Faso, Cameroon, Côte d'Ivoire, The Gambia, Guinea-Bissau, Nigeria, Senegal, Eswatini, Rwanda, and Togo. MSM were recruited by respondent-driven sampling and were eligible if they met country-specific requirements for age, area of residence, and self reported being assigned male sex at birth and having anal sex with a man in the past 12 months. Policy related to same-sex sexual behaviour for each country was categorised as not criminalised or criminalised. Countries were also categorised on the basis of recent reports of prosecutions related to same-sex sexual acts. Legal barriers were defined as those that legally prevented registration or operation of sexual orientation related civil society organisations (CSOs). Individual data on HIV testing history, HIV status, and stigma were collected via interviewer-administered sociobehavioural questionnaires and HIV testing. Multilevel logistic regression with random intercepts was used to assess the association between policies, recent prosecutions, legal barriers to CSOs, and HIV-related factors with adjusted odds ratios (aORs) and 95% CIs. Findings: Between Aug 3, 2011, and May 27, 2020, we recruited 8047 MSM with a median age of 23 years (IQR 21–27). 4886 (60·7%) lived in countries that criminalise same-sex sexual acts. HIV prevalence among MSM was higher in criminalised settings than non-criminalised settings (aOR 5·15, 95% CI 1·12–23·57); higher in settings with recent prosecutions than in settings without prosecutions (12·06, 7·19–20·25); and higher in settings with barriers to CSOs than without barriers to CSOs (9·83, 2·00–48·30). HIV testing or status awareness was not associated with punitive policies or practices. Stigma was associated with HIV status but did not consistently vary across legal environments. Disparities in HIV prevalence between MSM and other adult men were highest in punitive settings. Interpretation: Structural risks including discriminatory country-level policies, prosecutions, and legal barriers might contribute to higher HIV prevalence among MSM. Taken together, these data highlight the importance of decriminalisation and decreasing enforcement, alongside stigma reduction, as central to effective control for HIV. Funding: National Institutes of Health. Translation: For the French translation of the abstract see Supplementary Materials section.